SOCIO-ECONOMIC SITUATION IN THE NEIGHBORS OF SHAHRISBZ CITY DURING THE YEARS OF INDEPENDENCE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article scientifically analyzes and discusses information about the work done on socio-economic issues in the neighborhoods of Shahrisabz during the years of independence, as well as measures aimed at ensuring their implementation.